Estratégias empresariais comparadas: o caso de três mineradoras latino-americanas - Oliveira, Thais Regina Spanazzi de (2005)
Especially throughout the 1990s, Latin American countries adopted reforms with a view to economic liberalization and liberalization. This process allowed foreign investors to enter various sectors of these economies, including mining. In view of this, it was possible for mining companies to enter the global movement of the sector, namely, asset reorganization and formation of strategic alliances, especially with foreign investors. In the face of these changes, the intention was to analyze the business strategies of Latin American mining companies, in a context of growing openness and economic liberalization. In this sense, the objective of the work was to investigate, comparatively and in depth, which were the business strategies adopted by three important Latin American mining companies, namely: Companhia Vale do Rio Doce (CVRD, Brazil), Corporación Nacional dei Chile copper (Codelco, Chile) and the Compania de Minas Buenaventura (BVN, Peru). In turn, business strategies were broken down into four dimensions, although the interconnection between them is naturally recognized: z) Competitive Strategies: how the company operates in its main business; ii) Corporate Strategies: history, level, degree and type of diversification; zzz) Internationalization Strategies: the company's investment trajectory abroad; and zv) Cooperative Strategies: predominant type of developed strategic alliances. The main motivations for the preparation of the study are of two natures: one of a macroeconomic nature, since mining remains an important activity for Latin American countries; and another microeconomic, since this activity has received little attention from the literature on industrial organization.